Efektivitas Penerapan Model Kooperatif Tipe Think Pair Share terhadap Hasil Belajar Siswa SMA Negeri 8 Padang - Fitri, Dhea Syafrima; Wiza, Rahmi (Lembaga Yasin AlSys, 2023)
This research aims to see how effective the implementation of the think pair share type cooperative model is on student learning outcomes in PAI subjects in Class material and has an impact on low student learning outcomes. The sampling technique in this research used a purposive sampling technique. The data collection method in this research used pretest and posttest. The data in the research were analyzed using the paired sample t-Test. The research results showed that the control group obtained sig. (2-tailed) = 0.001 < 0.05, meaning that H0 is rejected and Ha is accepted, and in the experimental group a sig value is obtained. (2-tailed) = 0.001 < 0.05, meaning that H0 is rejected and Ha is accepted, which means that the application of the think pair share type cooperative learning model is effective in improving PAI learning outcomes in Class X of SMAN 8 Padang. Learning Islamic Religious Education using the think pair share type cooperative learning model is more effective than conventional learning models.